Spectroscopic ellipsometry studies on the optical constants of indium tin oxide films deposited under various sputtering conditions - Jung, YS (ELSEVIER SCIENCE SA, 2004)
In this research, ITO thin film samples were prepared under various DC magnetron sputtering conditions. Their optical constants were analyzed based on a model combining Drude and Lorentz oscillator terms. Lower amount of oxygen flow, moderate range of sputtering pressure, and higher deposition temperature resulted in lower refractive indices. It was revealed that the refractive indices of the films are closely related with their crystallographic orientations. The samples with higher refractive indices had more (222)-oriented crystallographic structures. In addition, based on X-ray diffraction (XRD) analyses, the difference in the refractive indices between bottom and upper layers was explained from graded crystallographic orientation. Extinction coefficients in the visible were closely related with the crystallinity of the films and their stoichiometry, and with carrier concentration measured by Hall effect in the near infrared. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: THIN-FILMS; STRUCTURAL-PROPERTIES; PHYSICS